2019
DOI: 10.1039/c8cp06315j
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing depolarization by tail substitution in an organic supramolecular ferroelectric

Abstract: The depolarization problem of a supramolecular organic ferroelectric is solved by simple molecular structure modification and blending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 51 publications
(74 reference statements)
2
53
0
1
Order By: Relevance
“…As seen in Fig. 5a, the small-signal d 33 (black open symbols) slightly deteriorates from around À4.7 pm V À1 to À3.5 pm V À1 with disorder. In contrast, the large-signal d 33 has a strong growing trend from À5 pm V À1 to À21 pm V À1 .…”
Section: Vs Remnant Polarization and Disordermentioning
confidence: 69%
See 2 more Smart Citations
“…As seen in Fig. 5a, the small-signal d 33 (black open symbols) slightly deteriorates from around À4.7 pm V À1 to À3.5 pm V À1 with disorder. In contrast, the large-signal d 33 has a strong growing trend from À5 pm V À1 to À21 pm V À1 .…”
Section: Vs Remnant Polarization and Disordermentioning
confidence: 69%
“…Considering a single self-assembled molecular stack, one would expect a positive piezoelectric response at the nanoscale due to the applied field rotating the amide dipoles further out-of-plane, which does not agree with the measured macroscopic negative piezoelectric constants. To this end, we have simulated the behavior of a single molecular stack consisting of 18 methyl-tailed BTAs using the energy minimization principle in molecular dynamics 33 and found that with increasing field, Fig. 3 Simulated field-induced axial lattice strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems tend to predominantly form smectic phases, again attributed to intermolecular hydrogen bonding between the amide groups. Indeed, the use of amide groups in structures such as benzene tricarboxamides (BTA) [19][20][21][22] , hydrazine derivatives [23][24][25][26][27][28] , or peptide residues [29][30][31] promotes columnar liquid crystal phases in which hydrogen bonding stabilises the columns.…”
Section: Page 1 Of 31mentioning
confidence: 99%
“…Based on the abovementioned studies, Kemerink's group further investigated some branched BTA analogs (Figure ). They expected that sterically hindered peripheral groups would reinforce the retention time.…”
Section: Columnar Lcs Based On Amide Derivativesmentioning
confidence: 99%